Carrots and sticks don't work : build a culture of employee engagements with the principles of RESPECT - Marciano, Paul L. (McGraw-Hill, 2010)
Advance praise for "Carrots and Sticks Don't Work": 'Paul Marciano provides a wealth of prescriptive advice that absolutely makes sense. You can actually open the book to any chapter and gain ideas for immediate implementation' - Beverly Kaye, coauthor of "Love 'Em or Lose 'Em". 'This book should be in the hands of anyone who has to get work done through other people! It's an invaluable tool for any manager at any level' - John L. Rice, Vice President Human Resources, Tyco International. '"Carrots and Sticks Don't Work" provides a commonsense approach to employee engagement. Dr. Marciano provides great real-world insights, data, and practical examples to truly bring the RESPECT model to life' - Renee Selman, President, Catalina Health Resources. 'The RESPECT model is one of the most dynamic, engaging, and thought-provoking employee engagement tools that I have seen. Dr. Marciano's work will help you provide meaningful long-term benefits for your employees, for your organization, and for yourself' - Andy Brantley, President and CEO, College and University Professional Association for Human Resources. 'This book provides clear advice and instruction on how to engage your team members and inspire them to a higher level of productivity, work satisfaction, and enjoyment. I am already utilizing its techniques and finding immediate positive changes' - Robert Roth, Director, Accounting and Reporting, Colgate Palmolive Company. The title says it all: "Carrots and Sticks Don't Work". Reward and recognition programs can be costly and inefficient, and they primarily reward employees who are already highly engaged and productive performers. Worse still, these programs actually decrease employee motivation because they can make individual recognition, rather than the overall success of the team, the goal. Yet many businesses turn to these measures first - unaware of a better alternative. So, when it comes to changing your organizational culture, carrots and sticks don't work! What does work is Dr. Paul Marciano's acclaimed RESPECT model, which gives you specific, low-cost, turnkey solutions and action plans - based on seven key drivers of employee engagement that are proven and supported by decades of research and practice - that will empower you to assess, troubleshoot, and resolve engagement issues in the workplace: recognition and acknowledgment of employees' contributions; empowerment via tools, resources, and information that set employees up to succeed; supportive feedback through ongoing performance coaching and mentoring; partnering to encourage and foster collaborative working relationships; expectations that set clear, challenging, and attainable performance goals; and consideration that lets employees know that they are cared about Trust in your employees' abilities, skills, and judgment. "Carrots and Sticks Don't Work" delivers the same proven resources and techniques that have enabled trainers, executives, managers, and owners at operations ranging from branches of the United States government to Fortune 500 corporations to twenty-person outfits to realize demonstrable gains in employee productivity and job satisfaction. When you give a little RESPECT you get a more effective organization, with reduced turnover and absenteeism and employees at all levels who are engaged, focused, and committed to succeed as a team. In short, you get maximum ROI from your organization's most powerful resource: its people!